2022
DOI: 10.1093/toxres/tfab127
|View full text |Cite
|
Sign up to set email alerts
|

Activation of canonical inflammasome complex by acute silica exposure in experimental rat model

Abstract: Silicosis is a chronic irreversible pulmonary disease caused by the inhalation of silica crystals in occupational settings in most cases. Persistent inflammation in the alveolar space is considered to be the major reason for tissue damage and lung fibrogenesis. The mechanisms by which silica exposure activates immune cells are not well understood. Here, we employed an in vivo silicosis disease model by intratracheal instillation of a large dose of silica suspension in rats and explored the involvement of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…They discovered that AIM2 activation is critical in silica’s ability to stimulate lung immune cells. 40 We found that LPS increased AIM2 expression compared to the control group. C/EBPβ knockdown suppressed AIM2 transcription.…”
Section: Discussionmentioning
confidence: 62%
“…They discovered that AIM2 activation is critical in silica’s ability to stimulate lung immune cells. 40 We found that LPS increased AIM2 expression compared to the control group. C/EBPβ knockdown suppressed AIM2 transcription.…”
Section: Discussionmentioning
confidence: 62%
“…Lysosomal acidification could play a pivotal role, as suggested by a study that showed that H + ATPase inhibitor bafilomycin A impedes activation stimulated by particulate matter [ 84 ]. This finding is further justified by the fact that the MSU can activate the inflammasome as it is responsible for the lysosomal acid environment leading to a massive propagation of Na + , resulting in an increased influx of water and cellular osmolarity and a reduction of the concentration of K + inside the cell [ 85 ].…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…Current evidence claims that cathepsin B, a molecule released by lysosomes, contributes to the activation of inflammasome as it is necessary for the release of IL-1β. Furthermore, it was found that inflammasome is not activated in macrophages as a result of particulate exposure if they are treated with a chemical inhibitor for cathepsin B called CA-074-Me [ 84 ].…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…Subsequently, the ingested SiO 2 particles are released and reintroduced by other macrophages, thus amplifying the vicious cycle of inflammation and cell death [ 6 ]. Depending on the duration of exposure to SiO 2 particles, silicosis can be subdivided into an acute inflammatory form characterized by silicosis deposition disorder and a chronic form characterized by pulmonary collagen deposition and pulmonary fibrotic remodeling [ 7 , 8 ]. In order to reduce the morbidity and mortality associated with irreversible progressive and incurable silicosis, new therapies are urgently needed to prevent long-term inflammation and collagen deposition in silicosis [ 1 ].…”
Section: Introductionmentioning
confidence: 99%